Twofold increase in Weibull modulus of hot-pressed Si3N4 ceramic by modified pressing profile - Kumar K.; Kim M.-J.; Park Y.-J.; Kim H.-N.; Ma H.J.; Lee J.-W.; Ko J.-W. (My University, 2025)
The strength reliability is a crucial factor, which limits ceramic materials' wider application as a structural component. The influence of different hot-pressing sintering schedules on the strength reliability of Si3N4 was investigated. Only the pressure profile was changed (maximum fixed to 20 MPa), while the temperature profile remained identical (maximum limited to 1800 °C). With the mere change in pressure profile more than twofold enhancement in the Weibull modulus was achieved. The flexural strength and the Weibull modulus were as high as 1199 ± 92 MPa and 16, respectively was attained. The variation in pressure profile resulted in a microstructure with contrasting grain size distributions. A link between microstructure (grain size variation, flaw size range, glass pocket size) and Weibull modulus was noted. To comprehend further, flexural strength and hardness on both top and side surfaces were analyzed. This study showed a simple strategy to enhance Si3N4 strength reliability; which maybe applicable to other materials as well. © 2022 Elsevier Ltd